Penerapan Prinsip Pembelajaran Mendalam (PM) berkesadaran (mindful), bermakna (meaningful), dan menggembirakan (joyful) dalam Mata Pembelajaran Bola Besar Cabang Olahraga Futsal - Deni Mudian; Arif Fajar Prasetiyo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to describe and analyze the application of deep learning principles in learning big ball sport futsal in the subject of Physical Education, Sports, and Health (PJOK). The principles of deep learning used include aspects of mindfulness, meaningfulness, and joy. This approach was chosen to overcome the challenge of low student engagement and understanding of sports learning materials, especially basic futsal techniques. The research method used is a quantitative descriptive method with a case study approach. The population in this study were all students of class VIII SMP Negeri 2 Haurgeulis, while the sample used were 32 students of class VIII B, selected purposively. The research instrument in the form of student activity observation sheets was used to assess the level of engagement, conceptual understanding, and learning atmosphere. The results showed that the application of mindful, meaningful, and joyful learning principles was able to significantly increase students' active participation in learning activities. Students became more focused and aware of the learning process (mindful), were able to relate the material learned to real experiences (meaningful), and felt joy and comfort during the learning process (joyful). Furthermore, there was an improvement in basic futsal technical skills such as passing, dribbling, and shooting. Students also demonstrated reflective skills in evaluating their learning process and outcomes. The classroom atmosphere became more positive and conducive to learning. Thus, it can be concluded that the application of mindful, meaningful, and joyful in-depth learning principles is effective in improving the quality of physical education (PJOK) learning. This approach not only develops students' cognitive and psychomotor aspects but also supports the affective aspects, which are essential in the physical education process.